Daucosterol derived from Cordyceps (a Traditional Chinese Medicine) as a possible lead compound for allergic transfusion reactions - Yang, Jian; Li, Ji-Xia; Song, Zhe; Xia, Xi-Yan (Bangladesh Journal of Pharmacology, 2015)
Allergic transfusion reaction is an anomaly that develops within several hours of transfusion which is usually treated by antihistamine. In the present study, we are looking into daucosterol, an extract of Traditional Chinese Medicine (TCM) Cordyceps, as a potential inhibitor of histidine decarboxylase. The approach of molecular docking and Molecular Dynamics Simulation (MDS) on a traditional anti-inflammatory Chinese medicine gave an atomic insight of the inhibition. The daucosterol was binding with a ?G of -3.17 Kcal/mol, to inhibit histamine synthesis by binding to histidine decarboxylase, possibly via the flexible catalytic loop. Such inhibitors that were designed to block the flexibility of the catalytic loop are potential candidates for further drug development program.